تأثير المهارات الناعمة في تعزيز الديمومة التنظيمية: دراسة استطلاعية لآراء عينة من القيادة الإدارية في دائرة صحة ديالي - محمود، ناجي عبدالستار; جاسم، عدنان سهيل (جامعة تكريت - كلية الإدارة والاقتصاد, 2021)
The study aimed to determine the relationship of the effect of the independent variable soft skills on the dependent variable, organizational permanence, in the researched health organization. The importance of the study is represented by addressing two important variables to determine the success and continuity of organizations, namely soft skills and organizational longevity. As the accumulation of knowledge has an effective role in achieving a work environment capable of keeping pace with all that is new in the field of work of organizations and achieving its objectives in a way that ensures achieving high performance. Through the soft skills in a way that ensures enhancing the durability and durability of the health organization. For the purpose of achieving the objectives of the study and answering its questions, a descriptive and analytical approach was used to arrive at the results, and the study was taken from the Diyala Health Department as a community. (180) questionnaires were distributed to the administrative leaders workers in Diyala Health Department, and recovered (160) questionnaire forms valid for analysis. The study adopted the questionnaire as a main tool, in addition to the interviews conducted by the researchers with a number of members of the research sample, and after collecting data and information and treating them statistically, the study reached a set of conclusions, the most important of which are: The effect of soft skills on organizational longevity.
هدفت الدراسة إلى تحديد علاقة تأثير المتغير المستقل المهارات الناعمة على المتغير المعتمد الديمومة التنظيمية، في المنظمة الصحية المبحوثة. وتمثلت أهمية الدراسة من خلال تناولها متغيرين مهمين لتحديد نجاح واستمرار المنظمات، وهما المهارات الناعمة والديمومة التنظيمية، إذ أن التراكم المعرفي له دور فعال في تحقيق بيئة عمل قادرة على مواكبة كل ما هو جديد في مجال عمل المنظمات وتحقيق أهدافها بطريقة تضمن تحقيق الأداء العالي من خلال المهارات الناعمة على نحو يضمن تعزيز متانة وديمومة المنظمة الصحية، ولغرض تحقيق أهداف الدراسة، والإجابة على تساؤلاتها، تم استخدم المنهج الوصفي التحليلي، للوصول إلى النتائج، واتخذت الدراسة من دائرة صحة ديالى مجتمعا لها، فقد تم توزيع (180) استبانة على القيادات الإدارية العاملين في دائرة صحة ديالى، واسترد منها (160) استمارة استبيان صالحة للتحليل، واعتمدت الدراسة الاستبانة أداة رئيسية، فضلا عن المقابلات التي أجراها الباحثان مع عدد من أفراد العينة المبحوثة، وبعد جمع البيانات والمعلومات ومعالجتها إحصائيا توصلت الدراسة إلى مجموعة من الاستنتاجات من أهمها: وجود تأثير للمهارات الناعمة على الديمومة التنظيمية.
Keywords: المهارات الناعمة -- القيادة الإدارية -- التنظيم الإداري -- المهارات القيادية -- المنظمات الصحية